Collection and separation of recyclable materials: potential and limitations of collector associations (Research, Society and Development, 2022)
This research aimed to describe the potentialities and limitations of 14 associations of recyclable material collectors and their inclusion in the selective collection in the city of Chapecó-SC. To this end, a qualitative and quantitative study was conducted. The collection of information occurred through a semi-structured questionnaire in the period between October and November 2020. The analyses were performed using the content categorization technique. Fourteen professionals from material recycling associations were interviewed. Based on the results obtained, the main potentialities are the legal constitution of the Internal Regulations and Constitution Bylaws of the Association of Recyclable Material Collectors, the construction of new sheds, and the loads of recyclable material received daily by the associations. It was observed as a limitation in the selective collection process the mixing of organic waste with the recyclable one, compromising the generation of income, and the non-use or inadequate use of individual protection equipment. All the actors interviewed need more information, training, and support from public managers to improve the conditions, management, income, and life.